Elevating Sugarcane Farming: Effects of Certified Seed Adoption on Production and Income in East Java, Indonesia - Sandita, Tia; Rachmina, Dwi; Tinaprilla, Netti (Agro Ekonomi, 2024)
The use of certified seed is essential for sugarcane agricultural intensification method, emphasizing input quality improvements. In this context, varietal validity has the potential to increase sugarcane output volumes and ensure quality variations. Therefore, this research aimed to analyze the variables affecting farmers' decisions on seed varieties, output, and revenue. The type of data used was cross-sectional with a sample of 1,763 respondents, consisting of 303 and 1,460 adopter and non-adopter farmers, respectively. Propensity score matching and logistic regression were the analysis methods used. The results showed that farmers' age, number of workers, land ownership status, extension participation, and partnerships significantly influenced the decisions in selecting seed types. Significant variations in output, gross income, total expenses, net income, and net earnings were also reported using statistical test analysis, with certified seed adopters having higher profits. In this context, young farmers should be targeted to promote the use of certified seed, provide sufficient labor support for intensive farming, ease access to land, and enhance persuasive messages about partnership benefits. Moreover, ensuring the continuity of production and distribution was important to maintain reasonable seed prices and facilitate farmers' access.